2014
DOI: 10.1016/j.comppsych.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a modified version of the PRIME screen for psychosis-risk symptoms in a non-clinical Kenyan youth sample

Abstract: Background The PRIME screen is a self-administered questionnaire designed to quickly assess individuals at risk for developing a psychotic disorder. It is shorter in both length and administration time compared to the Structured Interview for Psychosis-Risk Syndromes (SIPS)—a standard instrument for psychosis prodromal risk assessment. Validation of the PRIME against the SIPS has not been reported in large non-clinical populations. Methods A culturally modified version of the PRIME screen (mPRIME) was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…In this study, PPVs were relatively low for a predictable screening tool [ 27 , 28 ]. This result may be explained by the observation that PPVs were relatively high in studies of selected help-seeking samples visiting specialized prodrome clinics and community mental health clinics [ 27 , 28 ], and low in studies of subjects with no help-seeking behavior, similar to ours [ 19 , 29 , 30 ]. Therefore, investigators who wish to increase the PPV of the KPQ-16 may use a higher cutoff score, which would lower the false-positive rate and sensitivity.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, PPVs were relatively low for a predictable screening tool [ 27 , 28 ]. This result may be explained by the observation that PPVs were relatively high in studies of selected help-seeking samples visiting specialized prodrome clinics and community mental health clinics [ 27 , 28 ], and low in studies of subjects with no help-seeking behavior, similar to ours [ 19 , 29 , 30 ]. Therefore, investigators who wish to increase the PPV of the KPQ-16 may use a higher cutoff score, which would lower the false-positive rate and sensitivity.…”
Section: Discussionsupporting
confidence: 73%
“…Endorsement of positive items of the CAPE may reflect distress or affective dysregulation rather than psychosis risk. It may also be argued that the items of the CAPE should have been adapted to the local culture, but a study of a similar screening instrument that was culturally adapted, reported a poor sensitivity and a low positive predictive value of psychosis risk in Kenyan young adults [29]. We intended to use the CAPE for screening purposes in a subsequent incidence study of psychotic disorders in Vulindlela, in order to enrich the sample and reduce the number of individuals needing indepth diagnostic interviews.…”
mentioning
confidence: 99%
“…Assessing clinical risk early has significantly advanced the possibility of indicated prevention of full-blown psychotic disorders (Yung et al 1996(Yung et al , 2004Miller et al 1999). Our group has conducted multiple studies in Kenya, investigating the prevalence of PLEs and risk for developing illness using self-report questionnaires (Mamah et al , 2013Ndetei et al 2012;Owoso et al 2014). The Washington Early Recognition Center Affectivity and Psychosis (WERCAP) Screen ) was developed to overcome some of the challenges in assessing risk of developing psychotic disorders, guided by the existing literature on risk assessment and our previous efforts in Africa and the USA.…”
Section: Introductionmentioning
confidence: 99%